Election Night at Bruce Bronzan State Assembly Campaign Headquarters in Roos-Atkins Building - Watkins, Howard::::::::: (1978)
Supporters watching TV election returns: Nick Bronzan, Doug Broten, Nyla Hallum, Tony Correia, Bill Carlson, Bruce Bronzan, ?, Sandy Walsh, Randy Walsh, Doug Jones, ? (kneeling)